2017
DOI: 10.1039/c7ra02945d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary oxidized tyrosine products on insulin secretion via the oxidative stress-induced mitochondria damage in mice pancreas

Abstract: The findings suggested that decreased insulin secretion triggered by OTPs may be mediated by oxidative stress and mitochondrial damage in pancreatic β cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 63 publications
3
45
0
Order By: Relevance
“…Particular protein oxidation products, such as protein carbonyls, the α‐amino adipic acid, tyrosine, tryptophan, and phenylalanine oxidation products, among others, initially exposed to the intestinal mucosa, are absorbed and hence, accumulate in the epithelium and may be distributed to distant internal organs through the bloodstream (Ding, Cheng et al., , Ding, Li et al., ; Wang et al., ; Yang, Zhang et al., , Yang, Yan et al., ). The intestinal uptake of specific protein oxidation products after oral administration, and the subsequent organic accumulation proves the bioavailability and bioactivity of these species which seem to have certain tropism for target tissues.…”
Section: Dietary Protein Oxidation and Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…Particular protein oxidation products, such as protein carbonyls, the α‐amino adipic acid, tyrosine, tryptophan, and phenylalanine oxidation products, among others, initially exposed to the intestinal mucosa, are absorbed and hence, accumulate in the epithelium and may be distributed to distant internal organs through the bloodstream (Ding, Cheng et al., , Ding, Li et al., ; Wang et al., ; Yang, Zhang et al., , Yang, Yan et al., ). The intestinal uptake of specific protein oxidation products after oral administration, and the subsequent organic accumulation proves the bioavailability and bioactivity of these species which seem to have certain tropism for target tissues.…”
Section: Dietary Protein Oxidation and Oxidative Stressmentioning
confidence: 99%
“…The intestinal uptake of specific protein oxidation products after oral administration, and the subsequent organic accumulation proves the bioavailability and bioactivity of these species which seem to have certain tropism for target tissues. This is the case of protein carbonyls for the intestinal epithelium (Keshavarzian et al., ), the α‐amino adipic acid for pancreas (Wang et al., ), and oxidized tyrosines for pancreas, kidney and liver (Ding, Cheng et al., ; Ding, Li et al., ; Ding, Tang et al., ; Yang, Zhang et al., , Yang, Yan et al., ). Finally, it is worth noting that the elevation of protein oxidation markers in blood and tissues may not only be caused by the intake of such species.…”
Section: Dietary Protein Oxidation and Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…These tests generally include a minimum or maximum values for protein, moisture, or fat. Whereas studies examining dietary oxidized protein in broilers and rodents have shown decreased organ and immune function, the risks to livestock or companion animals that consume oxidized lipids and proteins are not well defined ( Wu et al, 2014 ; Li et al, 2016 ; Ding et al, 2017 ; Estévez and Luna, 2017 ; Yang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…and immune function. [16][17][18][19] These possible implications justify the need to understand how extrusion can impact protein oxidation.…”
Section: Studies Examining Dietary Oxidized Protein In Broilers and Rmentioning
confidence: 99%